1997
DOI: 10.1046/j.1471-4159.1997.69041417.x
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of Microtubule‐Associated Protein 1B Phosphorylation Sites Recognised by Monoclonal Antibody SMI‐31

Abstract: MAP 1 B is a microtubule-associated phosphoprotein that is expressed early in neurons and plays a role in axon growth. MAP 1 B has two types of phosphoisoforms, one of which is developmentally down-regulated after neuronal maturation and one of which persists into adulthood. Because phosphorylation regulates MAP 1 B binding activity, characterisation of the phosphorylation sites and identification of the corresponding kinases! phosphatases are important goals. We have characterised the developmentally down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…1) -corresponding to mouse MAP1B Journal of Cell Science 122 (14) amino acids 1244-1530, and therefore containing the S1388 and S1392 sites (Trivedi et al, 2005) -only after it has been phosphorylated in vitro with a neonatal rat brain extract containing MAP1B kinases (Fig. 2C) (Johnstone et al, 1997). We have previously shown that this is also true of SuperBUGS and BUGS (Trivedi et al, 2005).…”
Section: Production and Characterisation Of Phosphospecific Antibodiementioning
confidence: 79%
See 2 more Smart Citations
“…1) -corresponding to mouse MAP1B Journal of Cell Science 122 (14) amino acids 1244-1530, and therefore containing the S1388 and S1392 sites (Trivedi et al, 2005) -only after it has been phosphorylated in vitro with a neonatal rat brain extract containing MAP1B kinases (Fig. 2C) (Johnstone et al, 1997). We have previously shown that this is also true of SuperBUGS and BUGS (Trivedi et al, 2005).…”
Section: Production and Characterisation Of Phosphospecific Antibodiementioning
confidence: 79%
“…We purified MAP1B from neonatal rat brain (Johnstone et al, 1997) and mapped the phosphorylation sites by mass spectrometry. This MAP1B is a developmentally regulated microtubule-associated phosphoprotein that regulates microtubule dynamics in growing axons and growth cones.…”
Section: A Comparison Of the Phosphorylation Maps Of Juvenile And Adumentioning
confidence: 99%
See 1 more Smart Citation
“…5B and data not shown). We used an antibody that recognizes the total amount of MAP1B, independently of its phosphorylation state (Fischer and Romano-Clarke, 1990), and specific antibodies that distinguish the two types of MAP1B phosphorylation: the SMI31 monoclonal antibody for mode I (Johnstone et al, 1997), and the 125 monoclonal antibody specific to mode II (Ulloa et al, 1993). The protein levels of all MAP1B forms were reduced in the COUP-TFI null brains (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Lysates were assayed for GSK3b activity using a recombinant fragment of MAP1B (1B750) as a substrate (Johnstone et al 1997;Lucas et al 1998;Goold and Gordon-Weeks 2001). Extracts from cultures not treated with NGF were used as a negative control.…”
Section: Measurement Of Gsk3b Activitymentioning
confidence: 99%